2018
DOI: 10.1093/ofid/ofy327
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin-Guided Antibiotic Therapy Reduces Antibiotic Use for Lower Respiratory Tract Infections in a United States Medical Center: Results of a Clinical Trial

Abstract: BackgroundEuropean trials using procalcitonin (PCT)-guided antibiotic therapy for patients with lower respiratory tract infections (LRTIs) have demonstrated significant reductions in antibiotic use without increasing adverse outcomes. Few studies have examined PCT for LRTIs in the United States.MethodsIn this study, we evaluated whether a PCT algorithm would reduce antibiotic exposure in patients with LRTI in a US hospital. We conducted a controlled pre-post trial comparing an intervention group of PCT-guided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 23 publications
1
26
0
3
Order By: Relevance
“…For cases of proven bacterial etiology or high clinical suspicion of bacterial CAP, there is insufficient evidence to recommend the early discontinuation of antibiotics based on procalcitonin levels short of the recommended five-day course according to current guidelines. 10 Future clinical trials are needed to determine if procalcitonin guidance can safely decrease the duration of antibiotic therapy for confirmed bacterial CAP to less than five days.…”
Section: Resultsmentioning
confidence: 99%
“…For cases of proven bacterial etiology or high clinical suspicion of bacterial CAP, there is insufficient evidence to recommend the early discontinuation of antibiotics based on procalcitonin levels short of the recommended five-day course according to current guidelines. 10 Future clinical trials are needed to determine if procalcitonin guidance can safely decrease the duration of antibiotic therapy for confirmed bacterial CAP to less than five days.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 14 studies were included in the metaanalysis of PCT as a biomarker for COPD exacerbation ( Fig. 1) [6,[13][14][15][16][17][18][19][20][21][22][23][24][25]. Reasons for excluding studies are summarized in Supplementary Appendix 2; the most common reason for excluding a study was the lack of reported data specifically on COPD exacerbation.…”
Section: Overview Of Studiesmentioning
confidence: 99%
“…For observational studies, three studies used a before-after study design, and appropriate selection of a non-exposed group was unclear [13,18,25]. The existence of comorbidity was not comparable between exposed and non-exposed groups in one study [18].…”
Section: Quality Appraisal Of Clinical Studies Of Procalcitonin In Comentioning
confidence: 99%
“…Regarding antibiotic utilization, three other studies [7][8][9] have just been published after Pepper et al Huang et al 7 and van der Does et al 8 were randomized trials performed in the ED to evaluate antibiotic use; both failed to demonstrate antibiotic reduction with PCT. Both trials included a small number of patients with confirmed bacterial infection (30%-35%), low proportion of patients with pneumonia (20%-30%), low adherence with study protocol (60%-65%), a few patients who needed ICU admission (4%-5%), and very low mortality (2%-3%).…”
mentioning
confidence: 99%
“…In addition, the numerous PCT studies done over more than a decade for acute bronchitis and COPD exacerbation have demonstrated the efficacy and safety of short course of antibiotics, which has already changed the standard of care to just a few days of antibiotics now. 9 In more recent studies in COPD patients adjusting antibiotic duration according to standard of care recommendations in the control group, PCT algorithms failed to demonstrate reduction on antibiotic exposure. 10 Further, the case mix and the absence of critically ill patients indicate that neither of these two trials 7,8 would meet the inclusion criteria by Pepper et al The third study, by Towsend et al 9 had a quasiexperimental design that showed a significant reduction in antibiotic use in lower respiratory tract infections; however, this study's design would also not meet Pepper et al criteria.…”
mentioning
confidence: 99%